The genus Neisseria - Bennett, J; Bratcher, H; Brehony, C; Harrison, O; Maiden, M (Springer, 2014)
The genus Neisseria comprises a number of closely related Gram-negative organisms isolated from humans and animals. Their interrelationships are poorly resolved by phenotypic approaches, and the classification of the species groups by molecular techniques has been confused by a combination of their genetic similarity and extensive shared sequence polymorphism as a consequence of shared ancestry, horizontal genetic exchange, or both. Whole genome sequence analysis, especially of large numbers of draft genome sequences, has enabled the comparison of core genes across the genus, and this has proved to be an effective means of defining species groups within the genus. This redefinition is largely consistent with previous species designations with relatively few adjustments necessary. Most members of the genus are not, or are very rarely, pathogenic, but the genus contains the globally significant pathogens Neisseria meningitidis, the meningococcus, and Neisseria gonorrhoeae, the gonococcus. The meningococcus is an ‘‘accidental pathogen’’: predominantly existing as a harmless commensal, with very few infections resulting in pathology. Pathology does not appear to play a role in the transmission of this organism, although some genotypes have a greater propensity to cause disease than others. The majority of work on the genus concentrates on the two pathogenic species, with attempts to develop a comprehensive vaccine against the meningococcus a major driver for research. The gonococcus is antigenically highly diverse but genetically quite uniform, and probably emerged from a single clone that changed its niche. Emerging antibiotic resistance of the gonococcus currently represents the most significant global health challenge presented by this genus.